2001
DOI: 10.1046/j.1365-2036.2001.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole in children: pharmacokinetics and efficacy in reflux oesophagitis

Abstract: Background: Data on the proton pump inhibitor lansoprazole in paediatric patients are limited. Aim: To investigate the pharmacokinetics, optimal dosage and efficacy of lansoprazole in paediatric patients. Methods: A 24‐h gastric pH recording and a pharmacokinetic study were performed after 7 days of lansoprazole, 17 mg/m2, in 23 patients with reflux oesophagitis (median age, 3.5 years). Response was defined as pH > 3 for > 65% of the recording. The dosage was doubled in non‐responders. Patients with no respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 17 publications
9
46
0
Order By: Relevance
“…24,25 one study reported lansoprazole to be effective and safe in children with reflux oesophagitis, with an optimal starting dosage of 30 mg/m 2 or 1.4 mg/kg. 26 However, the use of lansoprazole for rAP treatment has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 one study reported lansoprazole to be effective and safe in children with reflux oesophagitis, with an optimal starting dosage of 30 mg/m 2 or 1.4 mg/kg. 26 However, the use of lansoprazole for rAP treatment has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…In those aged 1–10 years, a higher daily dosage is often necessary (2–2.5 mg/kg/day for omeprazole and 1.4 mg/kg/day for lansoprazole). Interindividual variability is observed as in adults [22, 23]. Clinical and biological tolerance is good, with side effects being mostly mild (e.g.…”
Section: Treatment Of Gor and Gord In Infants And Childrenmentioning
confidence: 99%
“…Clinical and biological tolerance is good, with side effects being mostly mild (e.g. 10–20% experience headache, constipation, diarrhoea or rash) [20, 21, 22, 23]. The safety of PPIs taken long term (mean 6.5 years) has been reported in adults but not in children [20, 21].…”
Section: Treatment Of Gor and Gord In Infants And Childrenmentioning
confidence: 99%
“…68 Lansoprazole has also been shown to improve symptoms and promote healing of esophagitis in children 4 months to 15 years of age with GERD refractory to H 2 RAs. [69][70][71] One study demonstrated that higher doses (1.3-1.5 mg/kg/day) had higher healing rates compared to lower doses (0.8-1 mg/kg/day). 69 Another study that measured the 24-hour intragastric pH in children ages 18 days to 14 years with GERD found that multiple daily doses provided greater acid suppression than did single daily doses.…”
Section: Proton Pump Inhibitorsmentioning
confidence: 99%
“…69 Another study that measured the 24-hour intragastric pH in children ages 18 days to 14 years with GERD found that multiple daily doses provided greater acid suppression than did single daily doses. 71 All agents in this class are believed to have similar effectiveness, but comparative studies and studies of newer agents like pantoprazole and rabeprazole in infants and children are not yet available.…”
Section: Proton Pump Inhibitorsmentioning
confidence: 99%